Effect of intonation on phonetic realization of lexical tones: experimental investigation of standard Latvian - Švageris, Evaldas (Baltistica, 2020)
The present paper deals with the question of how prosodic elements (lexical tones and phrase intonation in particular) interact with each other in acoustic terms. For this purpose the Latvian language was selected as an object. First, the main phonological problems in this area were addressed in order to select an appropriate method. The choice is based on the presumption that the type of prosodic information strongly depends on the time quantization level. In other words, differences of prosodic nature may be classified separately according to the time step adjusted for the analysis of tonal elements. Following this new methodology, lexical tones were examined in various intonational conditions. Final results lead to the following conclusions. 120 Firstly, there is a clear empirical basis to presuppose that the functional load plays an important role in establishing the difference level of lexical tones. Secondly, the pitch contour levelling indicates the negative impact of phrase intonation on lexical tones in some intonation types. Thirdly, the research data show that the pitch jerk and tone sustainability coefficient are those acoustic correlates which are capable of maintaining lexical tone separation to some degree in most intonational conditions.
Keywords: Latvian; acoustic phonetics; lexical tone; phrasal intonation; tone; slope; jerk